Local Bird Knowledge and Practices among Traditional Accipiter Hawkers of the Black Sea Coast of Transcaucasia - Sözüer, Özgün; Aktay-Sözüer, Lale; Lakerta, Refik; Bilgin, Sercan; Kurdoğlu, Oğuz (Ethnobiology Letters, 2025)
The traditional accipiter hawkers in the Arhavi district of Artvin province of Turkey and the Makhindjauri (მახინჯაური) village of Georgia were investigated to understand local knowledge and potential conservation of birds in these communities. Through free-listing, identification, pile sorting, and conducting unstructured interviews, our results revealed detailed, consistent, and specific knowledge of birds among the hawkers of both survey sites. All participants were male, as both hunting and hawking are gendered ancestral activities. Songbirds and diurnal raptors were the most common groups identified. The classification of birds was primarily functional, citing behavior and usage, especially edibility. The names of songbirds are more likely to be of non–Turkic origin, probably because of onomatopoeia, but most raptors have very functional Turkish names. We have concluded that this detailed, and consistent knowledge within the region could form a good foundation for effective and participatory conservation strategies in communication with the local hawkers.